The Role of Technological Innovation in Mediating The Influence of Intellectual Capital on MSMEs Business Performance - Astuti, Kartika Tri; Syah, Muhammad Fahmi Johan (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to examine the role of technological innovation variables in mediating the influence of intellectual capital consisting of 3, namely Human Capital, Structural Capital, and Customer Capital on MSME performance. Using simple random sampling, the number of respondents was 106 consisting of MSME owners, employees, and student business owners from the total population. The data collection technique used an online survey with instruments from previous studies and self-development instruments. The data analysis technique used the PLS-SEM method. The results show that the three structural capital variables have a significant effect on technological innovation and customer capital affects MSME performance. However, the results of the analysis show that technological innovation is not a significant mediator variable between the variables included in Intellectual Capital on MSME performance. This shows that, for the MSME level, the use of technology improves MSME performance but not significantly. The existence of technological innovation, although it strengthens the relationship between Human Capital, Structural Capital, and Customer Capital on MSME performance, does not have a significant impact. Practically, this is possible because the cash flow is not yet high so it can still be handled manually. These results still need to be further developed regarding the role of technology in the MSME sector, especially at the micro level. Further research can test more deeply and can divide into each micro, small and medium cluster.